Alzheimer's disease research progress in Australia: The Alzheimer's Association International Conference Satellite Symposium in Sydney. Issue 1 (31st May 2021) - Sexton, Claire E.; Anstey, Kaarin J.; Baldacci, Filippo; Barnum, C. J.; Barron, Anna M.; Blennow, Kaj; Brodaty, Henry; Burnham, Samantha; Elahi, Fanny M.; Götz, Jürgen; Jeon, Yun‐Hee; Koronyo‐Hamaoui, Maya; et al.
Abstract: The Alzheimer's Association International Conference held its sixth Satellite Symposium in Sydney, Australia in 2019, highlighting the leadership of Australian researchers in advancing the understanding of and treatment developments for Alzheimer's disease (AD) and other dementias. This leadership includes the Australian Imaging, Biomarker, and Lifestyle Flagship Study of Ageing (AIBL), which has fueled the identification and development of many biomarkers and novel therapeutics. Two multimodal lifestyle intervention studies have been launched in Australia; and Australian researchers have played leadership roles in other global studies in diverse populations. Australian researchers have also played an instrumental role in efforts to understand mechanisms underlying vascular contributions to cognitive impairment and dementia; and through the Women's Healthy Aging Project have elucidated hormonal and other factors that contribute to the increased risk of AD in women. Alleviating the behavioral and psychological symptoms of dementia has also been a strong research and clinical focus in Australia.